Pregled statusa in raziskanosti hroščev (Coleoptera) evropskega varstvenega pomena v Sloveniji s predlogom slovenskega poimenovanja - Vrezec, Al (Acta entomologica slovenica (Ljubljana), 2011)
Recent intensive research activity on beetles of conservation importance across Europe provided new knowledge also about their distribution ranges. In the contribution the list of species from appendices of Habitat directive occuring in Slovenia is revised. The revision listed 20 species for Slovenia belonging to 13 families: Rhysodidae, Carabidae, Dytiscidae, Leiodidae, Elateridae, Buprestidae, Cerambycidae, Lucanidae, Bolboceratidae, Scarabaeidae, Cucujidae, Meleandrydae and Bostrichidae. In the paper the proposal of Slovenian nomenclature, the overview of species biology and ecology and current knowledge over species status and occurrence in Slovenia is given. According to recent studies the overview of methods for species detection and sampling is provided. The general aim of the study is to stimulate research of considered species in Slovenia, since they are mainly poorly known and studied species.
Keywords: hrošči; metode vzorčenja; natura 2000; seznam vrst; slovenska imena